Insect pests of wild cranberry, Vaccinium macrocarpon, in Newfoundland and Labrador - Dixon, P.L.; Hillier, N.K. (Phytoprotection, 2002)
Cranberry (Vaccinium macrocarpon) has been commercially developed since the late 1990's in Newfoundland and Labrador. At that time, the insect fauna of the extensive stands of native, wild cranberry was not known, although these might provide a reservoir for pests to move to commercial sites. The occurrence and distribution of cranberry-feeding insects were assessed in wild stands to help cranberry growers prepare for the insect pests they might have to manage. Adults of the cranberry fruitworm, Acrobasis vaccinii were recovered in pheromone traps and larvae found in berries. The fruitworm was common and widespread. Moths of the cranberry girdler, Chrysoteuchia topiaria were caught in pheromone traps, but larvae were not recovered from plant or soil samples. There was no evidence of the black-headed fireworm, Rhopobota naevana, the cranberry weevil, Anthonomus musculus, the red-headed flea beetle, Systena frontalis, or the cranberry tipworm, Dasineura oxycoccana, serious cranberry pests in other areas. However, larvae of the lingonberry fruitworm, Grapholita libertina, were found infesting cranberry at one site in 1998. Of the species found in this study, A. vaccinii probably represents the most serious threat to the industry.